RANCANG BANGUN ADVENTURE LEGENDA GATOTKACA DENGAN METODE COLLISION DETECTION - Amin, Fatkhul Amin2; Saefuddin, Romi Saefuddin1 (Information Technology and Telematics, 2019)
Currently, puppet stories are less attractive by public because of the sophisticated technology developments. That matter, make people especially the children lazy to study and choose for playing the game in their smartphone. The writer take a initiative to make a game with the puppet concept and add education. Namely "Petualangan Legenda Gatotkaca" that purpose to increasing public awareness, towards Indonesian culture. The writer raised the puppet character Gatotkaca. He is a very popular puppet figure. For example in Javanese puppet, he is known as Gatotkoco (Javanese). His miracle is told extraordinary, including being able to fly in space without using wings, his nickname is famous called with wire muscle and iron bone. This game uses coillision detection method. The game model that is presented Gatotkaca as the main character, and there are 3 adventure levels in every level genre, that have different difficulties and information also questions in the end of the game. The writer has done the testing in android with 3 different types of specifications, and all of them can run the game " Gatotkaca Legend Adventure " smoothly. Research result show that "Gatotkaca Legend Adventure" made by Construct 2 can run easily in android platform